The role of Physical Internet on enabling sustainable multimodal logistics infrastructure: the case of sugar logistics in southeastern Brazil - Defina, Denise Alessandra (2018)
Brazilian logistics is the aim of this thesis, which includes discussion concerning main problems and difficulties faced by the Brazilian corporations with respect to transportation infrastrucuture, handling, storage, production and delivery for internal and external marketing. Verifying how Brazil can improve its logistics industry in order to achieve innovative forms of sustainability is the purpose of this discussion. On pursuing this path, historical data was obtained with respect to Brazilian logistics industry, which can partly explain the inefficiency of priority road as a single modal mean and pollution effects. An extensive literature review about sustainability, logistics, Physical Internet and transportation systems is carried out. Concepts from Physical Internet are studied in order to verify how logistics could be improved, national and international commercial relationships and social welfare as well. Through this research, it was possible to obtain evidences that an important Southeast located sugar cane plant uses a small percentage of its own transportation and private hired to distribute its final product. Road transportation covers internal market while road and overseas transportation is directed to external markets. Applying Physical Internet concepts like hyperconnected distribution network using Simulator Logistics Analytics 8, was determinant on verifying that is possible to make use of systemic distribution network, which complies with diverse sorts of multimodality demand and, at the same time, providing sustainability indicators. In Brazil\'s Southeast it would be possible if governmental and private actors could be interested on investing, maybe on a partnership basis, in a viability project.